Xylem vessel type and structure influence the water transport characteristics of Panax notoginseng - Tianyu Xu; Zonglei Li; Sanlin Bao; Yanru Su; Zhouming Su; Shuteng Zhi; Ennan Zheng (PLoS ONE, 2023)
Panax notoginseng plays a very important role in medicinal and economic value. The restriction imposed by the hydraulic pathway is considered to be the main limitation on the optimal growth state of Panax notoginseng. The flow resistance and water transport efficiency of vessel were affected by vessel type and secondary thickening structure. The vessel structure parameters of Panax notoginseng were obtained by experimental anatomy, and the flow resistance characteristics were analyzed by numerical simulation. The results showed that the xylem vessels had annular thickening and pit thickening walls. The flow resistance coefficient (ξ) of the pitted thickening vessel was significantly lower than that of annular thickening vessel in four cross-sectional types. The ξ of the circular cross-sectional vessel was the largest, followed by the hexagon, pentagon cross-sectional vessel and the lowest was the quadrilateral cross-sectional vessel, and the structure coefficient (S) was just the opposite. The ξ of the vessel model was positively correlated with the annular height, pitted width and pitted height, and negatively correlated with the annular inscribed circle diameter, annular width, annular spacing, pitted inscribed circle diameter and pitted spacing. Among them, annular (pitted) height and the annular (pitted) inscribed circle diameter had a great influence on the ξ. The increasing and decreasing trend of the S and ξ were opposite in the change of annular (pitted) inscribed circle diameter, and consistent in the change of in other structural parameters, indicating that the secondary wall thickening structure limited the inner diameter of the vessel to maintain a balance between flow resistance and transport efficiency.